MODERN APPROACHES FOR DEVELOPING LANGUAGE SKILLS IN FOREIGN LANGUAGE TEACHING - Farhodova Shahzoda Umid qizi; Toshboeva Malikabonu Abduvali kizi (TADQIQOTLAR, 2026)
Abstract:  This  article  examines  modern  approaches  to  developing  language skills  in  foreign  language  teaching.  The  study  focuses  on  innovative  pedagogical strategies that enhance learners’ listening, speaking, reading, and writing abilities in contemporary educational contexts. Emphasis is placed on communicative, cognitive, and technology-integrated approaches that support learner-centered instruction. The research  highlights  how  modern  methodologies  contribute  to  increased  learner motivation, autonomy, and communicative competence. The findings demonstrate that the effective integration of modern approaches significantly improves language skill development and overall learning outcomes.